Филогения жуков-щелкунов (Coleoptera, Elateridae) - Долин, В.Г. (Вестник зоологии, 1978)
The phylogeny of the Elateridae family is substantiated an the basis of studies in the fossil forms of click beetles of the recent world fauna and analysis of the larva marphology.